Higher Sun Exposure in the First Trimester Is Associated With Reduced Preterm Birth; A Scottish Population Cohort Study Using Linked Maternity and Meteorological Records - Megaw, Lauren; Clemens, Tom; Daras, Konstantinos; Weller, Richard B.; Dibben, Chris; Stock, Sarah Jane (Frontiers in Reproductive Health, 2021)
Background: Preterm birth (birth at less than 37 weeks gestation) is the leading cause of death in children under five years old and prevention is a global public health issue. Seasonal patterns of preterm birth have been reported, but factors underlying this have been poorly described. Sun exposure is an important environmental variable that has risks and benefits for human health, but the effects of sun exposure on pregnancy duration and preterm birth are unknown. Objectives: To determine the association between available sun exposure and preterm birth. Methods: We performed a population-based data-linkage study of 556 376 singleton births (in 397,370 mothers) at or after 24 weeks gestation, in Scotland between 2000-2010. Maternity records were linked to available sun exposure from meteorological records, by postcode. Logistic regression analysis was used to explore the relationship between available sunshine and preterm birth at less than 37 weeks gestation. Exploratory analyses included a subgroup analysis of spontaneous and indicated preterm births and a sibling analysis in sib-pairs discordant for preterm birth. Results: The rate of preterm birth was 6.0% (32 958/553 791 live births). Increased available sun exposure in the first trimester of pregnancy was associated with a reduced risk of preterm birth, with evidence of a dose response. Compared to the lowest quartile of sun exposure, the highest quartile of sun exposure was associated with a reduced odds ratio (OR) of preterm birth of 0.90 (95% Confidence Interval (CI) 0.88 – 0.94 p <0.01) on univariable analysis and OR 0.91 (95% CI 0.87, 0.93 p <0.01) after adjustment for second trimester sunlight exposure, parity, maternal age, smoking status and deprivation category. No association was seen between preterm birth and second trimester available sun exposure or combined first and second trimester exposure. Similar patterns were seen on sibling analysis and within both the indicated and spontaneous preterm subgroups. Discussion: Available sun exposure in the first trimester of pregnancy is associated with a protective effect on preterm birth less than 37 weeks gestation. This opens up new mechanisms, and potential therapeutic pathways, for preterm birth prevention.